2013
DOI: 10.2527/jas.2012-5638
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental vitamin C improves marbling in feedlot cattle consuming high sulfur diets

Abstract: The objective of this study was to examine the effects of supplemental rumen-protected vitamin C (VC) on live and carcass-based performance, and antioxidant capacity of cattle consuming varying concentrations of dietary S. Angus-cross steers (n = 120) were blocked by initial BW (341 ± 11 kg) and assigned equally to 1 of 6 treatments, evaluating 3 concentrations of dietary S [0.22%, 0.34%, and 0.55%, for low S (LS), medium S (MS), and high S (HS), respectively] and 2 concentrations of supplemental VC (0 or 10 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
69
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 36 publications
(45 reference statements)
8
69
5
Order By: Relevance
“…High S in the body has been identified as a potential cause in the development of oxidative stress, as evident by a depletion of glutathione (GSH; Truong et al, 2006;Pogge and Hansen, 2013), which may contribute to an oxidative environment postmortem. It is well established that a postmortem oxidative environment interferes with proteolysis thus hindering the tenderization process (Guttmann and Johnson, 1998;Lametsch et al, 2008;Rowe et al, 2004).…”
Section: Effects On Carcass and Meat Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…High S in the body has been identified as a potential cause in the development of oxidative stress, as evident by a depletion of glutathione (GSH; Truong et al, 2006;Pogge and Hansen, 2013), which may contribute to an oxidative environment postmortem. It is well established that a postmortem oxidative environment interferes with proteolysis thus hindering the tenderization process (Guttmann and Johnson, 1998;Lametsch et al, 2008;Rowe et al, 2004).…”
Section: Effects On Carcass and Meat Characteristicsmentioning
confidence: 99%
“…While it is well established that S negatively affects trace mineral status (Suttle, 1991), no research addresses the repercussions of high S diets on the integrity of the trace mineraldependent antioxidant enzymes. Pogge and Hansen (2013) However, while supplementation with antioxidants may decrease oxidative stress associated with high S diets, more research is needed to determine if cattle growth or carcass characteristics may be positively affected as well. Kung et al (2000) tested the effects of lasalocid and monensin (5 mg/L in culture fluid) on H 2 S production in vitro, and observed no effect of lasalocid but found that monensin increased the production of H 2 S. The culture fluid in this experiment contained 136 mg of S per L. However, when Quinn et al (2009) Smith et al (2010) are more likely to be encountered in vivo than that of Kung et al (2000).…”
Section: Antioxidantsmentioning
confidence: 99%
See 2 more Smart Citations
“…feedlot cattle (Smith et al 2013). However, high sulfur level in DDGS has become a potential limiting factor to its inclusion in cattle rations (Kwiatkowski et al 2006;Klopfenstein et al 2007) given that high sulfur content intake would exert a detrimental effect on animal performance and carcass quality Pogge and Hansen 2013), even the health status Pogge and Hansen 2013).…”
Section: Doi: 1017221/85/2016-cjasmentioning
confidence: 99%